Implementasi Alat Monitoring Kualitas Garam Berbasis Ramah Lingkungan pada Petani Tambak Ujung Pusong Jaya, Gampong Lancang Barat, Kecamatan Dewantara, Kabupaten Aceh Utara - Ula, Mutammimul; Salamah; Fajri , Riyadhul; Fadillah, Tengku Farhan; Juandana, Rio Adian (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The use of increasingly competitive digital media for MSMEs and monitoring seawater quality measurements in viewing water quality at each screw table can be an innovative solution to improve salt quality supervision. However, so far, measuring seawater quality using a baumemeter is still less effective in viewing water quality at each screw table and seeing the water level in each salt quality pool can be done in stages. The purpose of the Community Service is to find out how to apply a salt content measurement tool to environmentally friendly crystallization for Ujung Pusong Jaya pond farmers and can be done periodically at each salt screw table. Stages of the Location Survey method, permit management, and discussion of PKM Implementation, Determining the time and place of service, preparation of materials, modules, socialization, training in water quality monitoring tools, implementation of service. The results of this tool service are to facilitate and assist members of the Beumakmu pond farmer group in monitoring and monitoring levels periodically without dependence. Furthermore, the speed of information is a preventive effort in taking steps to minimize the risk of greater losses in viewing the quality of pond water at each screw table.